Participatory farmers’ selection of common bean varieties (Phaseolus vulgaris L.) under different production constraints - Awio, Bruno; Katungi, Enid M.; Nkalubo, Stanley T.; Mukankusi, Clare Mugisha; Malinga, Geoffrey Maxwell; Gibson, Paul; Rubaihayo, Patrick; Edema, Richard (Wiley, 2018)
On‐farm evaluation of 15 common bean varieties was undertaken with nine farmer groups under two fertilizer applications levels in four subcounties of Hoima and Rakai districts for two seasons to select farmers’ desired and undesired varieties. Farmers’ votes for acceptance and rejection of varieties at podding stage were converted to a preference index, and analysis of variance was conducted to examine differences in farmers’ preference indices among subcounties and combined across subcounties, seasons, management and gender. Management had no‐significant influence on the way farmers selected varieties in the subcounties. Choice of varieties varied significantly (p ≤ .001) between seasons and gender in the different subcounties. Variety Masindi Yellow Long and Farmers’ seed (Kaduli), and the introduced KATB1 were accepted by farmers due to their medium seed size, desired seed colour and potential of varietal adaptability to their farm conditions. Varieties NABE2, ROBA1 and RWR719 were deselected due to possession of traits less desired in the market. These results demonstrate the need for breeding programmes to involve diverse stakeholders in capturing the diverse traits preferences in varietal development process.